Privatização e trabalho no Brasil : o caso Escelsa (Espírito Santo Centrais Elétricas S.A) - Rizzi, Leonardo Effgen (2008)
It analyses and understands the consequences of the privatization for the workforce of the Escelsa, defining the roots of the quality of life in the work through the economical, political, psychological and sociological dimensions, in which an alternative model is formulated, where there were identified the factors what it intervenes in the conditions of the environment of work in the perception of the workers of the enterprise. The hard-working methodology went to the joining of the quantitative and qualitative approaches, through the application of a questionnaire for the collection of information. The results noted that the privatization provoked drastic changes in the culture organizational considering so in the capacity of life of the work of the employees and, out of the same thing.